Prophylactic crystalloids or prophylactic crystalloids with ephedrine: Comparison of hemodynamic effects during caesarean section under spinal anaesthesia using 0.5% bupivacaine - Bharath Kumar Hegde; Manjunath Timmappa Bhat (Wolters Kluwer Medknow Publications, 2017)
Background: Spinal anaesthesia is usually chosen for caesarean section not only because of its faster onset and reliability but also because general anaesthesia is associated with more complications. However, hypotension is one of the most common complications of spinal anaesthesia in obstetric patients. Several measures have been devised to prevent hypotension, which include left uterine displacement, infusion of crystalloids before giving spinal anaesthesia (preloading) and administration of a prophylactic vasopressor. This study compared the hemodynamic effects of preloading crystalloids or crystalloids with ephedrine for caesarean section under spinal anaesthesia using 0.5% bupivacaine. Materials and Method: In this randomized, single blind, comparative clinical study, 80 parturients (American Society of Anesthesiologists grade 1) presenting for elective caesarean section under spinal anaesthesia were allocated to one of the two groups; group I received crystalloid preload and group II received crystalloid with ephedrine before spinal block. After institution of spinal anaesthesia in the lateral position with 2.0 ml (10 mg) of bupivacaine, 0.5% (heavy) using 25 G Quincke type spinal needle, parturients were made to assume a supine position with left lateral tilt. Heart rate, systolic blood pressure and diastolic blood pressure were monitored intraoperatively every 2 minutes till delivery and every 5 minutes after delivery. The amount of ephedrine used intraoperatively was also noted and compared among different groups. Results: Incidence of hypotension was 70% in the crystalloid group and 5% in the crystalloid with ephedrine group. This difference between the two groups was statistically significant (P < 0.001). The number of patients receiving rescue bolus of ephedrine was higher in the crystalloid group (40% before delivery and 30% after delivery) compared to crystalloid with ephedrine group (5% before delivery and none after delivery); the difference was statistically significant (P < 0.001). Sixteen patients (40%) in the crystalloid group experienced nausea compared to 6 patients (15%) in the crystalloid with ephedrine group; the difference was statistically significant with a P value of 0.012. Conclusion: This study demonstrates that prophylactic ephedrine given by infusion along with crystalloids is not only a simple and effective method for prevention of hypotension during spinal anaesthesia during elective caesarean section in ASA Grade I patients but also contributes to less incidence of intraoperative nausea and vomiting.